Hubungan Durasi Penggunaan Media Sosial dengan Gangguan Kualitas Tidur Remaja di SMP Negeri 1 Mengwi - Kusmarini, Putu Elmamira; Indrasari Utami, Desak Ketut; Witari, Ni Putu; Eka Widyadharma, I Putu (Universitas Udayana, 2022)
The use of social media does have many advantages. But there are some bad effects that accompany it, one of which is sleep quality disturbances. A study shows that use of social media at night affects the quality of sleep worse, causing anxiety disorders, depression and self-esteem. Diagnosis of sleep disorders in adolescents is difficult because it is not often complained about by adolescents. In addition, when adolescents sleep disorders are no longer a concern for parents. In a study conducted by Haryono on junior high school students with 140 respondents, it was found that 63.6% experienced sleep disorders. This study aims to prove that there is a relationship between social media use and adolescent sleep quality disorders at SMP Negeri 1 Mengwi. This study used a cross sectional approach in which the independent and dependent variables were collected at one time and at the same time. The sample in this study amounted to 79 respondents who met the inclusion and exclusion criteria. From the results of the Correlation analysis test, it got a p value <0.05 with a correlation coefficient of 0.633 which indicates a strong positive relationship between the duration of social media use and the quality of sleep of the respondents. Based on the results of the research and discussion carried out, it can be concluded that there is a significant relationship between the duration of social media use and sleep quality in adolescents at SMP Negeri 1 Mengwi. Keywords: Social media, sleep quality disturbance, adolescent sleep quality